(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the relationships generally accepted notions of «information security», «protection of information» and unstudied terms related to computer technology «cyber security» and «cyber defense». The recommendations for the improvement of national legislation in the fi eld of cyber security in Kazakhstan. Key words: cyber security, cyberspace, cyber defense, information, security, communication networks.